The infinite in the summa theologica: theology, physics and mathematics - Gómez Camacho, Francisco (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
This article presents the doctrine of St. Thomas about the idea of the infinite in the Summa Theologica, question 7ª: «The Infinity of God». The doctrine is presented from three different perspectives, following the different articles of this question: first, as a theological problem (art. 1: «Whether God is infinite»); second, as a physical problem (art. 2: «Whether anything but God can be essentially infinite»); and finally, as an analysis of a mathematical problem (arts. 3 and 4: «Whether an actually infinite magnitude can exist», and «Whether an infinite multitude of thing can exist»). This presentation, therefore, intends to be an interdisciplinary.